Frontal sinus approach in complicated Chronic Rhinosinusitis with Nasal Polyps: our experience - Maksim Aflitonov; Aleksei Voronov; Vladimir Dvoryanchikov; Sergei Artyushkin; Evgeniyav Bezrukova (Babol University of Medical Sciences, 2023)
Background: Hyperostosis is a common consequence of chronic rhinosinusitis with nasal polyps (CRSwNP) and other chronic rhinosinusitis, affecting mainly structures of the ethmoid labyrinth, frontal and maxillary sinuses. These neo-bones are found in advanced stages of rhinosinusitis causes exacerbation because of ostia outflow blockage. Frequent relapses of the disease due to hyperostosis restenosis, represent a problem in the treatment of chronic frontal sinusitis. We report our cases experience about the treatment of frontal chronic sinusitis because of frontoethmoidal area hyperostosis, treated by modified lothrop procedure, achieving sufficient clinical effect. Case Presentation: A 52-year-old female (CRSwNP) with right side frontoethmoidal area totally obstructed by 25 × 15 × 10 mm bony mass, with total opacification of the right frontal and left maxillary sinuses, right frontal sinus anterior wall defect. A 63-year-old male (CRSwNP) with a 23 × 10 × 10 mm bony mass arising from the right frontoethmoidal area which causes total opacification of the right frontal sinus, inferior and posterior sinus wall defect. Conclusion: Modified lothrop procedure is a method of choice for frontoethmoidal bone hyperostosis surgery to be performed endoscopically. Endoscopy provides excellent visualization of anatomy and a better approach to bone hyperostosis zone.